2021
DOI: 10.3390/microorganisms9051013
|View full text |Cite
|
Sign up to set email alerts
|

Rehydration before Application Improves Functional Properties of Lyophilized Lactiplantibacillus plantarum HAC03

Abstract: Preservation of probiotics by lyophilization is considered a method of choice for developing stable products. However, both direct consumption and reconstitution of dehydrated probiotic preparations before application “compromise” the survival and functional characteristics of the microorganisms under the stress of the upper gastro-intestinal tract. We evaluated the impact of different food additives on the viability, mucin adhesion, and zeta potential of a freeze-dried putative probiotic, Lactiplantibacillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…In these circumstances, the media composition plays a key role in the rate of cell growth. This is particularly relevant in the case of massive use of lyophilized microorganisms, for instance as biofertilizers in agriculture, where rehydration of lyophilized cells before their application improves functional properties ( Arellano-Ayala et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these circumstances, the media composition plays a key role in the rate of cell growth. This is particularly relevant in the case of massive use of lyophilized microorganisms, for instance as biofertilizers in agriculture, where rehydration of lyophilized cells before their application improves functional properties ( Arellano-Ayala et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the use of lyophilized microorganisms, it should be noted that lyophilization is the optimal method for preserving microorganisms and their use is of great interest in sectors such as agriculture, where the use of lyophilized microorganisms for the treatment of plant pathologies, to promote plant growth and enhance biotic and abiotic stress resistance is increasingly widespread (Ma et al, 2021). It has been reported that rehydration of lyophilized cells before their application improves functional properties (Arellano-Ayala et al, 2021). For both cases, DNA transformation and rehydration of lyophilized cells, enriched media, such as SOC or 2YT, are required.…”
Section: Discussionmentioning
confidence: 99%
“…Rehydration conditions have long been known to affect the viability of lyophilized bacteria ( Font De Valdez et al, 1985 ), however little is known about their impact on probiotic activity ( Broeckx et al, 2016 ). However, recent evidence coming from the gastrointestinal field suggests that both function and adhesion can be enhanced by prior rehydration ( Arellano-ayala et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…While ISO standards exist for evaluating (gastrointestinal) probiotic supplements ( Binda et al, 2020 ), there are no guidelines or standards for determining an effective dose for probiotics for oral health that accounts for losses through washout. While the exact mechanisms are not fully understood, rehydrating the probiotic before administration is advantageous for probiotics for gastrointestinal ( Arellano-ayala et al, 2021 ) and potentially oral health. Providing optimal reconstitution conditions may enhance their function ( Muller et al, 2010 ; Broeckx et al, 2016 ) and possibly boost their adhesion potential.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies around the world have revealed that a variety of factors influence the survival of freeze–dried LAB, which can be summarized as follows: bacterial characteristics, culture conditions, centrifugation parameters, pretreatment methods, selection of protectants, freeze–drying parameters, water content, storage and rehydration conditions, etc. (Arellanoayala et al, 2021; Lee et al, 2016). Among them, the selection and optimization of protectants were the key to the research.…”
Section: Introductionmentioning
confidence: 99%